Improvement of Viability of Lactobacillus casei and Bifidobacterium longum with Several Encapsulating Materials using Extrusion Method - . Widaningrum; . Miskiyah; D Indrasti; HC Hidaya (Jurnal Ilmu Ternak dan Veteriner, 2018)
Lactobacillus casei and Bifidobacterium longum are probiotics commonly applied as dry starter for food system. Drying process in the production of dry starter can reduce the number of probiotics, therefore they are necessary to be encapsulated. Aim of this research was to obtain best encapsulating material for both probiotics. Encapsulation technique used in this research was extrusion with maltodextrine-alginate, sago starch-alginate, corn starch-alginate, and control of treatment skim milk-alginate (w:w) as encapsulating materials.  The four encapsulating materials significantly affected the value of viability, encapsulation efficiency, number of cell in wet beads and dry beads, number of survival cell during drying process, and number of survival encapsulated cell in simulated acid and bile salt conditions. Based on viability of L. casei and B. longum, beads matrix characteristic, number of cell in wet beads and dry beads, and number of survival cells during drying process, maltodextrine-alginate was better than sago starch-alginate and corn starch-alginate, but was not as good as skim milk-alginate (control of treatment) as encapsulating material. Viability (number) of L. casei and B. longum in dry beads of maltodextrine-alginate were 4.69±0.08 log CFU/g and 5.32±0.21 log CFU/g, while number of L. casei and B. longum in dry beads of skim milk-alginate were higher 5.08±0.07 log CFU/g and 6.20±0.16 log CFU/g. L. casei more resistant than B. longum against acidic (low pH) environment. In the presence of 0.3% bile salt, L. casei and B. longum encapsulated with skim milk-alginate increased as much as 2.75±0. 02 and 1.61±0.04 log cycles, respectively.